In vitro micropropagation and gas chromatography-mass spectrometry profiling of callus culture in Pulicaria jaubertii for conservation and metabolite production - Fathia, Mohamed Noman Salam; Fatima, Ahmed Alhadi; Ebraheem Ali, Al-nawd; Enas Jabir, Al-sanabani; Esam, Mohammed Aqlan; Majed Ahmed, Al-Mansoub (Open Science Publishers LLP, 2025)
Pulicaria jaubertii is an aromatic and medicinal plant endemic to Yemen, currently facing habitat decline. This study aimed to evaluate its in vitro response in full-strength Murashige and Skoog (medium supplemented with different types and concentrations of plant growth regulators. Among the tested plant parts, only seed explants successfully initiated callus formation. Calli were subsequently subcultured in media containing 0.1 mg/L 1-naphthaleneacetic acid (NAA) with kinetin (Kin) at 0, 0.25, 0.5, or 1 mg/L. Additional experiments tested media with 0.1 mg/L 6-benzylaminopurine and indole-3-acetic acid (IAA) (0–1 mg/L), as well as 0.1 mg/L Kin with 2,4-dichlorophenoxyacetic acid (2,4-D) (0–1 mg/L). Growth parameters related to callus induction, root, shoot, and leaf production were assessed. Findings revealed that Kin had no significant effect on most growth parameters except callus colour (P = 0.012), with the best growth at 0.25 mg/L. Similarly, IAA significantly influenced callus induction (P = 0.009), with optimal results at 1.0 mg/L. In contrast, 2,4-D had no significant effect, but its highest concentration (1.0 mg/L) supported optimal growth. Gas chromatography-mass spectrometry (GC-MS) analysis identified 46 compounds in the ethanolic callus extract compared to 25 in the mother plant, which indicates a richer phytochemical profile in the callus. The 2-Ethoxyethylamine (85.60%) and Stigmasterol (58.79%) were most abundant in ethanolic and n-hexane extracts. In conclusion, P. jaubertii seeds are the most responsive explants for micropropagation, forming callus as an initial step. Interestingly, GC-MS profiling identified bioactive compounds with medicinal properties. Further studies should refine auxin and cytokinin ratios to enhance propagation efficiency.